Microswimmers: Confined Catalytic Janus Swimmers in a Crowded Channel: Geometry‐Driven Rectification Transients and Directional Locking (Small 42/2016). Issue 42 (7th November 2016) - Yu, Hailing; Kopach, Andrii; Misko, Vyacheslav R.; Vasylenko, Anna A.; Makarov, Denys; Marchesoni, Fabio; Nori, Franco; Baraban, Larysa; Cuniberti, Gianaurelio
Abstract : Combining catalytic Janus swimmers and passive beads in narrow channels, L. Baraban and co‐workers observe many dynamic properties, ranging from distinct bulk and boundary‐free diffusivity at low densities, whereby a Janus swimmer transports large clusters of passive particles. This research (on page 5882) is an important milestone towards understanding and further fabrication of realistic bioinspired complex networks, containing synthetic autonomous micro‐ and nano‐ machines to perform the tasks in a mixture with passive objects. Image created by Julian Schütt.